Analisis Pengembangan Kurikulum Bahasa Arab Perguruan Tinggi Islam Di Indonesia - Mohamad Ghozi (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
Every curriculum that is carried out must have a negative and positive side that needs to be evaluated and improved to achieve better education goals. Basically the curriculum change is based on two ways, namely by replacing the overall components of the curriculum, or replacing just a few components. a curriculum includes elements of purpose, lecture material, learning process, evaluation, and government policies all of which are intended to develop the potential of students. These elements indicate the number of variables that affect the curriculum. Therefore, the Arabic language curriculum at PTA and PTU should accommodate a number of changes that occur in the community, the needs of the workforce, government policies in the world of education, and potential characteristics of students.